WITHDRAWN: Fast compressive tracking with robust example selection based on multiple instance learning in smart and autonomous systems. (September 2017) - Jia, Min; Gao, Zheng; Guo, Qing; Gu, Xuemai
Abstract : This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error. The full Elsevier Policy on Article Withdrawal can be found athttp://www.elsevier.com/locate/withdrawalpolicy .